A new glimpse of FadR-DNA crosstalk revealed by deep dissection of the E. coli FadR regulatory protein. Issue 12 (15th October 2014) - Zhang, Yongchang; Gao, Rongsui; Ye, Huiyan; Wang, Qingjing; Feng, Youjun
Abstract: Escherichia coli ( E. coli ) FadR regulator plays dual roles in fatty acid metabolism, which not only represses the fatty acid degradation ( fad ) system, but also activates the unsaturated fatty acid synthesis pathway. Earlier structural and biochemical studies of FadR protein have provided insights into interplay between FadR protein with its DNA target and/or ligand, while the missing knowledge gap ( esp. residues with indirect roles in DNA binding) remains unclear. Here we report this case through deep mapping of old E. coli fadR mutants accumulated. Molecular dissection of E. coli K113 strain, a fadR mutant that can grow on decanoic acid (C10) as sole carbon sources unexpectedly revealed a single point mutation of T178G in fadR locus (W60G in FadRk113 ). We also observed that a single genetically-recessive mutation of W60G in FadR regulatory protein can lead to loss of its DNA-binding activity, and thereby impair all the regulatory roles in fatty acid metabolisms. Structural analyses of FadR protein indicated that the hydrophobic interaction amongst the three amino acids (W60, F74 and W75) is critical for its DNA-binding ability by maintaining the configuration of its neighboring two β-sheets. Further site-directed mutagenesis analyses demonstrated that the FadR mutants (F74G and/or W75G) do not exhibit the detected DNA-binding activity, validating above structural reasoning.